One‐Pot Synthesis of N‐Substituted Enaminones from Ketones, Aromatic Nitriles and Halides. Issue 44 (27th November 2019) - Duan, Xiyan; Yang, Shijie; Yao, Changyang; Jia, Fenglin; Wang, Lin; Li, Weinan; Meng, Zhen; Zhou, Yingying; Li, Xiaoqing
Abstract: A simple and convenient one‐pot copper‐catalyzed synthesis of N ‐substituted enaminones has been demonstrated from ketones, aromatic nitriles and halides. This transformation involves the aldol‐type reaction and Ullmann‐type cross coupling, which features high efficient and inexpensive Cu‐catalyst with broader diversification scope. Abstract : A simple and convenient one‐pot copper‐catalyzed synthesis of N ‐substituted enaminones via a cascade C‐C bond and C‐N bond formation from ketones, aromatic nitriles and halides was described. This transformation involves the aldol‐type reaction and Ullmann‐type cross coupling, which features high efficient, inexpensive and nontoxic Cu‐catalyst with broader diversification scope. This transformation features easy accessibility of starting material, a broad substrate scope, and a less expensive catalyst and ligand, which should be applicable in organic chemistry and medical chemistry.